VARIASI ARUS TERHADAP KEKUATAN TARIK DAN BENDING PADA HASIL PENGELASAN SM490 - Syahrani, Awal; Sam, Alimuddin; Chairulnas, Chairulnas (Jurnal MEKANIKAL, 2013)
This study aimed to determine the effect of variations in welding current on tensile strength and bending the steel SM490, with the variation of welding current 140 A, 150 A, and 160 A. Electrodes used were E 7018, with the hem V angle 70o, SMAW welding methods. Tests performed are tensile and bending tests. The research was conducted at the department of materials science laboratory machine tadulako university engineering faculty. Ultimate tensile strength of welded joints occur at 160 A current variation with an average value of 626.35 MPa tensile stress and the lowest in the group of 140 A current variation of 468.85 MPa, and for an extension or tensile strain is highest value at 160 A by 14.33% and the lowest at 140 A current variation of 9.25%. To the elasticity of the welding process with a variation of the current value of 140 A bona fide high of 3260.03 MPa and the lowest was at 160 A current variation in the amount of 3040.64 MPa. Highest bending stress values ​​contained in the variation of welding current 160 A of 45.069 MPa and the lowest was at 140 A current variation of 40.635 Mpa. Deflection value that occurs in the bending test is highest value at 160 A current variation of 34.333 mm and the lowest was at 140 A current variation of 32.77 mm.